Die Expertenbewertung als Alternative zur Kontingenzbewertung; Expert valuation as an alternative to contingent valuation - Stefan Mann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– A lot of research is carried out on the Contingent Valuation Method to assess environmental goods. However, the method is rarely applied to quantify reimbursements for agri-environmental policy. In this paper, this contradiction is explained by conceptual shortcomings of the Contingent Valuation. It is suggested to discuss the utility of agri-environmental programs among experts. For that, a three-step methodology including a possible monetary evaluation is developed. The method is applied on agri-environmental programs in Switzerland.
Keywords: 330; Natürliche Ressourcen; Zahlungsbereitschaftsanalyse; Experten; Umweltpolitik; Agrarpolitik; Schweiz